Composite brake shoe material and preparation method thereof

By using specific formulas and process processing in synthetic brake shoe materials, a material with high bonding ability and stable friction performance is formed, which solves the problem of large fluctuation of friction coefficient during braking in the prior art, and achieves more stable braking performance and higher friction coefficient.

CN119912194APending Publication Date: 2025-05-02DALIAN JIAOTONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510273711.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing synthetic brake shoe materials fluctuate greatly during the braking process, and the braking stability is poor.

Method used

A formula of synthetic gate shoe material is adopted, including phenolic resin powder, nitrile rubber, styrene butadiene rubber and other components, and a cured intermediate product is formed through hot pressing and post-treatment processes, and finally high-temperature insulation is carried out in the oven to improve bonding ability and friction performance.

Benefits of technology

The friction stability of synthetic brake shoe materials at different braking speeds is improved, the fluctuations in friction coefficient are reduced, the material's wear resistance, high temperature resistance and aging resistance are enhanced, and the stability and high friction coefficient are ensured during braking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912194A_ABST
    Figure CN119912194A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of friction material preparation, in particular to a composition brake shoe material and a preparation method thereof. Potassium feldspar, wollastonite, sepiolite, basalt fibers, potassium titanate whiskers, bauxite, molybdenum disulfide, crystalline flake graphite, steel wool, reduced iron powder, electrolytic copper powder, vermiculite, barite, sulfur, zinc oxide, stearic acid and an accelerant. The preparation method comprises the steps of raw material weighing, mixing, hot pressing, putting into a drying oven and the like. The prepared composition brake shoe material is free of metal inlaying and other problems in use, the friction property of the obtained composition brake shoe material is greatly improved, and the composition brake shoe material has the advantages that the friction coefficient is slightly influenced by the braking speed, the stability is high, the material strength is high, the heat stability is good, the abrasion loss is low, and metal inlaying is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of friction material preparation. Background Art

[0002] The instantaneous friction coefficient of brake shoe materials is related to a series of factors such as the characteristics of each component material during the friction process, the coupling effect caused by physical and chemical changes between materials, and the flow change process of the product (wear debris) attached to the friction surface to form a third body. The relationship between the components is quite complex. The current synthetic brake shoes usually use phenolic resin and rubber as the base material, and add various friction performance modifiers to improve their friction performance. However, in the prior art, the instantaneous friction coefficient in high-speed braking increases in the early stage as the vehicle speed decreases, and the friction coefficient is small in the later stage due to the attenuation of the friction material, and the instantaneous friction coefficient in the low-speed braking process increases as the vehicle speed decreases. The prepared synthetic brake shoes have the problem of large fluctuations in the instantaneous friction coefficient during a single braking process and poor braking stability. Summary of the invention

[0003] In order to overcome the technical problems in the prior art that the friction coefficient of synthetic brake shoes fluctuates greatly during braking and the braking stability is poor, the present invention provides a synthetic brake shoe material and a preparation method thereof.

[0004] The technical scheme adopted by the present invention to achieve the above-mentioned purpose is: a synthetic brake shoe material, comprising the following raw material components in weight percentage: 8% to 12% of phenolic resin powder, 4% to 6% of nitrile rubber, 2% to 4% of styrene butadiene rubber, 2% to 4% of potassium feldspar, 4% to 6% of wollastonite, 3% to 5% of sepiolite, 3% to 5% of basalt fiber, 3% to 5% of potassium titanate whisker, 1% to 2.5% of bauxite, 2% to 3% of molybdenum disulfide, 8% to 9% of flake graphite, 15% to 20% of steel wool, 8% to 10% of reduced iron powder, 5% to 8% of electrolytic copper powder; 2% to 2.5% of vermiculite, 11% to 14% of barite, 0.3% of sulfur, 0.5% of zinc oxide, 0.5% of stearic acid and 0.2% of accelerator.

[0005] Preferably, the mass ratio of the phenolic resin powder, nitrile rubber and styrene-butadiene rubber is 4:3:2.

[0006] Preferably, the mass ratio of potassium feldspar, wollastonite, sepiolite, bauxite, vermiculite and barite is 8:8:6:2:5:28.

[0007] Preferably, the mass ratio of the basalt fiber to the potassium titanate whisker is 3:5.

[0008] Preferably, the mass ratio of the flake graphite to molybdenum dioxide is 8:3.

[0009] Preferably, the mass ratio of the steel wool, reduced iron powder and electrolytic copper powder is 20:8:5.

[0010] A method for preparing a synthetic brake shoe material comprises the following steps:

[0011] S1: Weigh the following raw material components in weight percentage at room temperature: 8% to 12% phenolic resin powder, 4% to 6% nitrile rubber, 2% to 4% styrene butadiene rubber, 2% to 4% potassium feldspar, 4% to 6% wollastonite, 3% to 5% sepiolite, 3% to 5% basalt fiber, 3% to 5% potassium titanate whisker, 1% to 2.5% bauxite, 2% to 3% molybdenum disulfide, 8% to 9% flake graphite, 15% to 20% steel wool, 8% to 10% reduced iron powder, 5% to 8% electrolytic copper powder; 2% to 2.5% vermiculite, 11% to 14% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator;

[0012] S2: Mix all the raw materials in step S1 to obtain a mixture 1;

[0013] S3: transferring the mixture 1 into a mold for hot pressing, demolding after hot pressing, and cooling to room temperature to obtain a solidified intermediate product 1;

[0014] S4: Place the intermediate product 1 in an oven for post-processing: start the oven, and raise the oven temperature to 160°C at a rate of 1°C to 2°C per minute, and keep it at 160°C for 6 hours, then turn off the oven, wait for the temperature in the oven to cool to 60°C, obtain the final synthetic brake shoe material, and take the final synthetic brake shoe material out of the oven.

[0015] Preferably, the mixing in step S2 is carried out using a flying knife type three-dimensional double-motion mixer, wherein the flying knife speed is set to 1000 r / min and the mixing time is 10 minutes.

[0016] Preferably, in step S3, the temperature of hot pressing is 145° C. to 160° C., the pressure of hot pressing is 15 MPa, and the hot pressing time is 50 minutes.

[0017] Compared with the prior art, the invention has the beneficial effect that the molecular chains of nitrile rubber and styrene butadiene rubber are broken by the strong shear force during the friction process, and a curing reaction occurs with sulfur and accelerators in the chemical additives under the action of friction heat, so that new molecular chains are formed in a short time, so that the nitrile rubber and styrene butadiene rubber are blended at the friction interface. This process consumes part of the friction heat, and the nitrile rubber and styrene butadiene rubber blend generated at the same time has the characteristics of wear resistance, high temperature resistance, weather resistance and anti-aging ability, and enhances the bonding ability of the system, and adds metal fillers to increase the friction coefficient. The steel wool is matched with reduced iron powder and electrolytic copper powder to utilize the good plasticity of metal copper. Under the action of shear force during the friction process, a copper particle layer is formed on the friction surface, which plays a role in heat conduction and heat dissipation when matched with iron powder and steel wool, especially during high-speed braking, reduces the influence of friction heat on the brake shoe material, stabilizes the friction coefficient, and the flake graphite and molybdenum disulfide, which are both layered structures, have an excellent effect on improving the friction stability of the brake shoe material under a specific ratio.

[0018] The synthetic brake shoe material prepared by the present invention ensures that the coupling effect generated by the synthetic brake shoe material during low-speed braking and high-speed braking allows the material to maintain a relatively high friction coefficient while reducing the difference between the friction coefficients at different speeds. No problems such as metal inlay occur during use, so that the friction of the obtained synthetic brake shoe material is greatly improved. It has the advantages that its friction coefficient is less affected by the braking speed, has high stability, high material strength, good thermal stability, low wear, and no metal inlay. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a curve diagram of the change of the average friction coefficient of each brake at different braking speeds for the synthetic brake shoe materials prepared in Example 1, Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2 of the present invention.

[0020] Figure 2 The synthetic brake shoe material prepared in Example 1 of the present invention is subjected to braking simulation at 50 km / h, 60 km / h and 140 km / h, and instantaneous friction coefficient curves at different braking speeds are plotted.

[0021] Figure 3 The synthetic brake shoe material prepared in Example 2 of the present invention was subjected to braking simulation at 50 km / h, 60 km / h and 140 km / h, and instantaneous friction coefficient curves at different braking speeds were plotted.

[0022] Figure 4 The synthetic brake shoe material prepared in Example 3 of the present invention was subjected to braking simulation at 50 km / h, 60 km / h and 140 km / h, and instantaneous friction coefficient curves at different braking speeds were plotted.

[0023] Figure 5The synthetic brake shoe material prepared in Example 4 of the present invention was subjected to braking simulation at 50 km / h, 60 km / h and 140 km / h, and instantaneous friction coefficient curves at different braking speeds were plotted.

[0024] Figure 6 The synthetic brake shoe material prepared in Comparative Example 1 of the present invention is subjected to braking simulation at 50 km / h, 60 km / h and 140 km / h respectively, and instantaneous friction coefficient curves at different braking speeds are plotted.

[0025] Figure 7 The synthetic brake shoe material prepared in Comparative Example 2 of the present invention was subjected to braking simulation at 50 km / h, 60 km / h and 140 km / h, and instantaneous friction coefficient curves at different braking speeds were plotted. DETAILED DESCRIPTION

[0026] The specific implementation of a synthetic brake shoe material and a preparation method thereof of the present invention is as follows:

[0027] Embodiment 1:

[0028] A synthetic brake shoe material comprises the following raw material components in percentage by weight: 8% phenolic resin powder, 6% nitrile rubber, 4% styrene-butadiene rubber, 4% potassium feldspar, 4% wollastonite, 3% sepiolite, 3% basalt fiber, 5% potassium titanate whisker, 1% bauxite, 3% molybdenum disulfide, 8% flake graphite, 20% steel wool, 8% reduced iron powder, 5% electrolytic copper powder; 2.5% vermiculite, 14% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator.

[0029] A method for preparing a synthetic brake shoe material comprises the following steps:

[0030] S1: Weigh the following raw material components in weight percentage at room temperature: 8% phenolic resin powder, 6% nitrile rubber, 4% styrene-butadiene rubber, 4% potassium feldspar, 4% wollastonite, 3% sepiolite, 3% basalt fiber, 5% potassium titanate whisker, 1% bauxite, 3% molybdenum disulfide, 8% flake graphite, 20% steel wool, 8% reduced iron powder, 5% electrolytic copper powder; 2.5% vermiculite, 14% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator, wherein the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide;

[0031] S2: All the raw materials in step S1 are mixed using a three-dimensional double-motion mixer with a flying knife, wherein the flying knife speed is set to 1000 r / min and the mixing time is 10 minutes to obtain a mixture 1;

[0032] S3: transferring the mixture 1 into a mold for hot pressing at a temperature of 160° C., a pressure of 10 MPa, and a time of 50 minutes. After hot pressing, demolding is performed and the mixture is cooled to room temperature to obtain a solidified intermediate product 1.

[0033] S4: Place the intermediate product 1 in an oven for post-processing: start the oven, and raise the oven temperature to 160°C at a rate of 1°C per minute, and keep it at 160°C for 6 hours, then turn off the oven, wait for the temperature in the oven to cool to 60°C, obtain the final synthetic brake shoe material, and take the final synthetic brake shoe material out of the oven.

[0034] Embodiment 2:

[0035] A synthetic brake shoe material comprises the following raw material components in percentage by weight: 8% phenolic resin powder, 6% nitrile rubber, 4% styrene-butadiene rubber, 4% potassium feldspar, 4% wollastonite, 3% sepiolite, 3% basalt fiber, 5% potassium titanate whisker, 1% bauxite, 3% molybdenum disulfide, 8% flake graphite, 20% steel wool, 8% reduced iron powder, 5% electrolytic copper powder; 2.5% vermiculite, 14% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator.

[0036] A method for preparing a synthetic brake shoe material comprises the following steps:

[0037] S1: Weigh the following raw material components in weight percentage at room temperature: 8% phenolic resin powder, 6% nitrile rubber, 4% styrene-butadiene rubber, 4% potassium feldspar, 4% wollastonite, 3% sepiolite, 3% basalt fiber, 5% potassium titanate whisker, 1% bauxite, 3% molybdenum disulfide, 8% flake graphite, 20% steel wool, 8% reduced iron powder, 5% electrolytic copper powder; 2.5% vermiculite, 14% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator, wherein the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide;

[0038] S2: All the raw materials in step S1 are mixed using a three-dimensional double-motion mixer with a flying knife, wherein the flying knife speed is set to 1000 r / min and the mixing time is 10 minutes to obtain a mixture 1;

[0039] S3: transferring the mixture 1 into a mold for hot pressing at a temperature of 145° C., a pressure of 15 MPa, and a time of 50 minutes, demolding the mixture after hot pressing, and cooling the mixture to room temperature to obtain a solidified intermediate product 1;

[0040] S4: Place the intermediate product 1 in an oven for post-processing: start the oven, and raise the oven temperature to 160°C at a rate of 1°C per minute, and keep it at 160°C for 6 hours, then turn off the oven, wait for the temperature in the oven to cool to 60°C, obtain the final synthetic brake shoe material, and take the final synthetic brake shoe material out of the oven.

[0041] Embodiment 3:

[0042] A synthetic brake shoe material comprises the following raw material components in percentage by weight: 12% phenolic resin powder, 4% nitrile rubber, 2% styrene-butadiene rubber, 2% potassium feldspar, 6% wollastonite, 5% sepiolite, 5% basalt fiber, 3% potassium titanate whisker, 2.5% bauxite, 2% molybdenum disulfide, 9% flake graphite, 15% steel wool, 10% reduced iron powder, 8% electrolytic copper powder; 2% vermiculite, 11% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator.

[0043] A method for preparing a synthetic brake shoe material comprises the following steps:

[0044] S1: Weigh the following raw material components in weight percentage at room temperature: 12% phenolic resin powder, 4% nitrile rubber, 2% styrene-butadiene rubber, 2% potassium feldspar, 6% wollastonite, 5% sepiolite, 5% basalt fiber, 3% potassium titanate whisker, 2.5% bauxite, 2% molybdenum disulfide, 9% flake graphite, 15% steel wool, 10% reduced iron powder, 8% electrolytic copper powder; 2% vermiculite, 11% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator, wherein the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide;

[0045] S2: All the raw materials in step S1 are mixed using a three-dimensional double-motion mixer with a flying knife, wherein the flying knife speed is set to 1000 r / min and the mixing time is 10 minutes to obtain a mixture 1;

[0046] S3: transferring the mixture 1 into a mold for hot pressing at a temperature of 145° C., a pressure of 15 MPa, and a time of 50 minutes, demolding the mixture after hot pressing, and cooling the mixture to room temperature to obtain a solidified intermediate product 1;

[0047] S4: Place the intermediate product 1 in an oven for post-processing: start the oven, and increase the oven temperature to 160°C at a rate of 2°C per minute, and keep it at 160°C for 6 hours, then turn off the oven, wait for the temperature in the oven to cool to 60°C, obtain the final synthetic brake shoe material, and take the final synthetic brake shoe material out of the oven.

[0048] Embodiment 4:

[0049] A synthetic brake shoe material comprises the following raw material components in percentage by weight: 10% phenolic resin powder, 5% nitrile rubber, 3% styrene-butadiene rubber, 3% potassium feldspar, 5% wollastonite, 4% sepiolite, 4% basalt fiber, 4% potassium titanate whisker, 2% bauxite, 2.5% molybdenum disulfide, 8.5% flake graphite, 17.5% steel wool, 9% reduced iron powder, 7% electrolytic copper powder; 2% vermiculite, 12% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator.

[0050] A method for preparing a synthetic brake shoe material comprises the following steps:

[0051] S1: Weigh the following raw material components in weight percentage at room temperature: 10% phenolic resin powder, 5% nitrile rubber, 3% styrene-butadiene rubber, 3% potassium feldspar, 5% wollastonite, 4% sepiolite, 4% basalt fiber, 4% potassium titanate whisker, 2% bauxite, 2.5% molybdenum disulfide, 8.5% flake graphite, 17.5% steel wool, 9% reduced iron powder, 7% electrolytic copper powder; 2% vermiculite, 12% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator, wherein the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide;

[0052] S2: All the raw materials in step S1 are mixed using a three-dimensional double-motion mixer with a flying knife, wherein the flying knife speed is set to 1000 r / min and the mixing time is 10 minutes to obtain a mixture 1;

[0053] S3: transferring the mixture 1 into a mold for hot pressing at a temperature of 160° C., a pressure of 10 MPa, and a time of 50 minutes. After hot pressing, demolding is performed and the mixture is cooled to room temperature to obtain a solidified intermediate product 1.

[0054] S4: Place the intermediate product 1 in an oven for post-processing: start the oven, and increase the oven temperature to 160°C at a rate of 2°C per minute, and keep it at 160°C for 6 hours, then turn off the oven, wait for the temperature in the oven to cool to 60°C, obtain the final synthetic brake shoe material, and take the final synthetic brake shoe material out of the oven.

[0055] Embodiment 5:

[0056] A synthetic brake shoe material comprises the following raw material components in percentage by weight: 10% phenolic resin powder, 5% nitrile rubber, 3% styrene-butadiene rubber, 3% potassium feldspar, 5% wollastonite, 4% sepiolite, 4% basalt fiber, 4% potassium titanate whisker, 1.75% bauxite, 2.5% molybdenum disulfide, 8.5% flake graphite, 17.5% steel wool, 9% reduced iron powder, 6.5% electrolytic copper powder; 2.25% vermiculite, 12.5% ​​barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator.

[0057] A method for preparing a synthetic brake shoe material comprises the following steps:

[0058] S1: Weigh the following raw material components in weight percentage at room temperature: 10% phenolic resin powder, 5% nitrile rubber, 3% styrene-butadiene rubber, 3% potassium feldspar, 5% wollastonite, 4% sepiolite, 4% basalt fiber, 4% potassium titanate whisker, 1.75% bauxite, 2.5% molybdenum disulfide, 8.5% flake graphite, 17.5% steel wool, 9% reduced iron powder, 6.5% electrolytic copper powder; 2.25% vermiculite, 12.5% ​​barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator, wherein the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide;

[0059] S2: All the raw materials in step S1 are mixed using a three-dimensional double-motion mixer with a flying knife, wherein the flying knife speed is set to 1000 r / min and the mixing time is 10 minutes to obtain a mixture 1;

[0060] S3: transferring the mixture 1 into a mold for hot pressing at a temperature of 150° C., a pressure of 13 MPa, and a time of 50 minutes. After hot pressing, demolding is performed and the mixture is cooled to room temperature to obtain a solidified intermediate product 1.

[0061] S4: Place the intermediate product 1 in an oven for post-processing: start the oven, and increase the oven temperature to 160°C at a rate of 1.5°C per minute, and keep it at 160°C for 6 hours, then turn off the oven, wait for the temperature in the oven to cool to 60°C, obtain the final synthetic brake shoe material, and take the final synthetic brake shoe material out of the oven.

[0062] Comparative Example 1:

[0063] A synthetic brake shoe material comprises the following raw material components in percentage by weight: 6% phenolic resin powder, 3% nitrile rubber, 1% styrene-butadiene rubber, 6% potassium feldspar, 8% wollastonite, 2% sepiolite, 2% basalt fiber, 6% potassium titanate whisker, 0.5% bauxite, 1% molybdenum disulfide, 10% flake graphite, 25% steel wool, 11% reduced iron powder, 3.5% electrolytic copper powder; 3.5% vermiculite, 10% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator.

[0064] A method for preparing a synthetic brake shoe material comprises the following steps:

[0065] S1: weigh the following raw material components in weight percentage at room temperature: 6% phenolic resin powder, 3% nitrile rubber, 1% styrene-butadiene rubber, 6% potassium feldspar, 8% wollastonite, 2% sepiolite, 2% basalt fiber, 6% potassium titanate whisker, 0.5% bauxite, 1% molybdenum disulfide, 10% flake graphite, 25% steel wool, 11% reduced iron powder, 3.5% electrolytic copper powder; 3.5% vermiculite, 10% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator, wherein the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide;

[0066] S2: All the raw materials in step S1 are mixed using a three-dimensional double-motion mixer with a flying knife, wherein the flying knife speed is set to 1000 r / min and the mixing time is 10 minutes to obtain a mixture 1;

[0067] S3: transferring the mixture 1 into a mold for hot pressing at a temperature of 160° C., a pressure of 13 MPa, and a time of 50 minutes, demolding the mixture after hot pressing, and cooling the mixture to room temperature to obtain a solidified intermediate product 1;

[0068] S4: Place the intermediate product 1 in an oven for post-processing: start the oven, and increase the oven temperature to 160°C at a rate of 1.5°C per minute, and keep it at 160°C for 6 hours, then turn off the oven, wait for the temperature in the oven to cool to 60°C, obtain the final synthetic brake shoe material, and take the final synthetic brake shoe material out of the oven.

[0069] Comparative Example 2:

[0070] A synthetic brake shoe material comprises the following raw material components in percentage by weight: 15% phenolic resin powder, 8% nitrile rubber, 5% styrene-butadiene rubber, 1% potassium feldspar, 2% wollastonite, 6% sepiolite, 7% basalt fiber, 2% potassium titanate whisker, 4% bauxite, 4% molybdenum disulfide, 6% flake graphite, 10.5% steel wool, 3% reduced iron powder, 9% electrolytic copper powder; 1% vermiculite, 15% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator.

[0071] A method for preparing a synthetic brake shoe material comprises the following steps:

[0072] S1: Weigh the following raw material components in weight percentage at room temperature: 15% phenolic resin powder, 8% nitrile rubber, 5% styrene-butadiene rubber, 1% potassium feldspar, 2% wollastonite, 6% sepiolite, 7% basalt fiber, 2% potassium titanate whisker, 4% bauxite, 4% molybdenum disulfide, 6% flake graphite, 10.5% steel wool, 3% reduced iron powder, 9% electrolytic copper powder; 1% vermiculite, 15% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator, wherein the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide;

[0073] S2: All the raw materials in step S1 are mixed using a three-dimensional double-motion mixer with a flying knife, wherein the flying knife speed is set to 1000 r / min and the mixing time is 10 minutes to obtain a mixture 1;

[0074] S3: transferring the mixture 1 into a mold for hot pressing at a temperature of 145° C., a pressure of 13 MPa, and a time of 50 minutes. After hot pressing, demolding is performed and the mixture is cooled to room temperature to obtain a solidified intermediate product 1.

[0075] S4: Place the intermediate product 1 in an oven for post-processing: start the oven, and increase the oven temperature to 160°C at a rate of 2°C per minute, and keep it at 160°C for 6 hours, then turn off the oven, wait for the temperature in the oven to cool to 60°C, obtain the final synthetic brake shoe material, and take the final synthetic brake shoe material out of the oven.

[0076] The synthetic brake shoe materials prepared in Example 1, Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2 were subjected to braking simulation at 50 km / h, 60 km / h and 140 km / h, respectively, and the instantaneous friction coefficient curves at different braking speeds were plotted. The results are shown in FIG. Figure 2-Figure 7 As shown, Figure 1The graphs are the variation curves of the average friction coefficient of each brake at different braking speeds for the synthetic brake shoe materials prepared in Example 1, Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2.

[0077] The usage of the synthetic brake shoe material prepared in Example 1 is shown in Table 1:

[0078] Table 1 Usage of the synthetic brake shoe material prepared in Example 1

[0079]

[0080] As shown in Table 1, the synthetic brake shoe material prepared in Example 1 has no metal inlay, cracks or block falling after braking, and the material wear amount is 0.17 cm 3 / MJ, the instantaneous friction coefficient curves at different braking speeds are as follows Figure 2 As shown, the friction coefficient curve is stable, and the difference between high-speed and low-speed braking friction coefficients is small, indicating that the synthetic brake shoe material has excellent friction stability;

[0081] The usage of the synthetic brake shoe material prepared in Example 2 is shown in Table 2:

[0082] Table 2 Usage of the synthetic brake shoe material prepared in Example 2

[0083]

[0084] As shown in Table 2, the synthetic brake shoe material prepared in Example 2 has no metal inlay, cracks or block falling after braking, and the material wear amount is 0.18 cm 3 / MJ, the instantaneous friction coefficient curves at different braking speeds are as follows Figure 3 As shown, the friction coefficient curve is stable, and the difference between high-speed and low-speed braking friction coefficients is small, indicating that the synthetic brake shoe material has high friction stability;

[0085] The usage of the synthetic brake shoe material prepared in Example 3 is shown in Table 3:

[0086] Table 3 Usage of the synthetic brake shoe material prepared in Example 3

[0087]

[0088] As shown in Table 3, the synthetic brake shoe material prepared in Example 3 has no metal inlay, cracks or block falling after braking, and the material wear amount is 0.20 cm 3 / MJ, the instantaneous friction coefficient curves at different braking speeds are as follows Figure 4 As shown, the friction coefficient curve is stable, and the difference between high-speed and low-speed braking friction coefficients is small, indicating that the synthetic brake shoe material has high friction stability;

[0089] The usage of the synthetic brake shoe material prepared in Example 4 is shown in Table 4:

[0090] Table 4 Usage of the synthetic brake shoe material prepared in Example 4

[0091]

[0092] As shown in Table 4, the synthetic brake shoe material prepared in Example 4 has no metal inlay, cracks or block falling after braking, and the material wear amount is 0.19 cm 3 / MJ, the instantaneous friction coefficient curves at different braking speeds are as follows Figure 5 As shown, the friction coefficient curve is stable, and the difference between high-speed and low-speed braking friction coefficients is within the allowable range, indicating that the synthetic brake shoe material has high friction stability;

[0093] The usage of the synthetic brake shoe material prepared in Example 5 is shown in Table 5:

[0094] Table 5 Usage of the synthetic brake shoe material prepared in Example 4

[0095]

[0096] As shown in Table 5, the synthetic brake shoe material prepared in Example 5 has no metal inlay, cracks or block falling after braking, and the material wear amount is 0.20 cm 3 / MJ.

[0097] The usage of the synthetic brake shoe material prepared in Comparative Example 1 is shown in Table 6:

[0098] Table 6 Usage of the synthetic brake shoe material prepared in Comparative Example 1

[0099]

[0100] As shown in Table 6, the synthetic brake shoe material prepared in Comparative Example 1 has no metal inlay after braking, but has cracks and falling blocks, and the material wear amount is 0.60 cm 3 / MJ, the wear is high, and the instantaneous friction coefficient curves at different braking speeds are as follows Figure 6 As shown in the figure, the instantaneous friction coefficient curve has a higher friction coefficient at low speeds, and is stable before 100 km / h at a high speed of 140 km / h, with high repeatability. When the speed is lower than 100 km / h, the friction coefficient begins to be dispersed. When the friction speed is lower than 50 km / h, the friction coefficient decreases rapidly and thermal decay occurs.

[0101] The usage of the synthetic brake shoe material prepared in Comparative Example 2 is shown in Table 7:

[0102] Table 7 Usage of the synthetic brake shoe material prepared in Comparative Example 2

[0103]

[0104] It can be seen from Table 7 that the synthetic brake shoe material prepared in the comparative example has no block falling phenomenon after braking, but there are metal inlay and crack phenomena, and the material wear amount is 0.26cm 3 / MJ, the wear amount is acceptable, and the instantaneous friction coefficient curves at different braking speeds are as follows Figure 7 As shown in the instantaneous friction coefficient curve, the friction coefficient is stable at low speed and the difference is small. The dispersion becomes larger at a high speed of 140km / h. When the friction speed is lower than 25km / h, thermal decay occurs.

[0105] like Figure 1 As shown, at different braking speeds, the average friction coefficients of Example 1, Example 2, Example 3 and Example 4 are slightly different. The average friction coefficients of Comparative Examples 1 and 2 fluctuate greatly at different braking speeds, indicating that at different braking speeds, the brake shoe material is affected by frictional heat, and the contribution of each component to the friction performance of the material varies. In Comparative Example 1, the proportion of metal filler is relatively large, and in Comparative Example 2, the proportion of binder is relatively large. The components of the two comparative examples are not within the optimal proportion range. Since the frictional heat cannot be removed in time, the friction coefficient is high during low-speed braking, and the friction coefficient is significantly reduced during high-speed braking, with large fluctuations. Figure 2-Figure 7 It can be seen that the synthetic brake shoe materials prepared in Example 1 and Example 2 have the best stability of friction coefficient and the lowest wear amount, which shows that the ratio and the preparation process parameters are optimal.

[0106] The present invention is described by way of embodiments, and those skilled in the art will appreciate that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application belong to the protection scope of the present invention.

Claims

1. A synthetic brake shoe material, characterized in that: The invention comprises the following raw material components in percentage by weight: 8% to 12% of phenolic resin powder, 4% to 6% of nitrile rubber, 2% to 4% of styrene-butadiene rubber, 2% to 4% of potassium feldspar, 4% to 6% of wollastonite, 3% to 5% of sepiolite, 3% to 5% of basalt fiber, 3% to 5% of potassium titanate whisker, 1% to 2.5% of bauxite, 2% to 3% of molybdenum disulfide, 8% to 9% of flake graphite, 15% to 20% of steel wool, 8% to 10% of reduced iron powder, 5% to 8% of electrolytic copper powder, 2% to 2.5% of vermiculite, 11% to 14% of barite, 0.3% of sulfur, 0.5% of zinc oxide, 0.5% of stearic acid and 0.2% of accelerator.

2. A synthetic brake shoe material according to claim 1, characterized in that: The mass ratio of the phenolic resin powder, nitrile rubber and styrene-butadiene rubber is 4:3:

2.

3. A synthetic brake shoe material according to claim 1, characterized in that: The mass ratio of potassium feldspar, wollastonite, sepiolite, bauxite, vermiculite and barite is 8:8:6:2:5:

28.

4. A synthetic brake shoe material according to claim 1, characterized in that: The mass ratio of the basalt fiber to the potassium titanate whisker is 3:

5.

5. A synthetic brake shoe material according to claim 1, characterized in that: The mass ratio of the flake graphite to molybdenum dioxide is 8:

3.

6. A synthetic brake shoe material according to claim 1, characterized in that: The mass ratio of the steel wool, reduced iron powder and electrolytic copper powder is 20:8:

5.

7. A method for preparing a synthetic brake shoe material as claimed in claim 1, characterized in that: The following steps are involved: S1: Weigh the following raw material components in weight percentage at room temperature: 8% to 12% phenolic resin powder, 4% to 6% nitrile rubber, 2% to 4% styrene butadiene rubber, 2% to 4% potassium feldspar, 4% to 6% wollastonite, 3% to 5% sepiolite, 3% to 5% basalt fiber, 3% to 5% potassium titanate whisker, 1% to 2.5% bauxite, 2% to 3% molybdenum disulfide, 8% to 9% flake graphite, 15% to 20% steel wool, 8% to 10% reduced iron powder, 5% to 8% electrolytic copper powder; 2% to 2.5% vermiculite, 11% to 14% barite, 0.3% sulfur, 0.5% zinc oxide, 0.5% stearic acid and 0.2% accelerator; S2: Mix all the raw materials in step S1 to obtain a mixture 1; S3: transferring the mixture 1 into a mold for hot pressing, demolding after hot pressing, and cooling to room temperature to obtain a solidified intermediate product 1; S4: Place the intermediate product 1 in an oven for post-processing: start the oven, and raise the oven temperature to 160°C at a rate of 1°C to 2°C per minute, and keep it at 160°C for 6 hours, then turn off the oven, wait for the temperature in the oven to cool to 60°C, obtain the final synthetic brake shoe material, and take the final synthetic brake shoe material out of the oven.

8. The method for preparing a synthetic brake shoe material according to claim 7, characterized in that: In step S2, a three-dimensional double-motion mixer with a flying knife is used for mixing, wherein the speed of the flying knife is set to 1000 r / min and the mixing time is 10 minutes.

9. The method for preparing a synthetic brake shoe material according to claim 7, characterized in that: In step S3, the temperature of hot pressing is 145° C. to 160° C., the pressure of hot pressing is 10-15 MPa, and the hot pressing time is 50 minutes.